2012
DOI: 10.1093/annonc/mdr385
|View full text |Cite
|
Sign up to set email alerts
|

Two escalated followed by six standard BEACOPP in advanced-stage high-risk classical Hodgkin lymphoma: high cure rates but increased risk of aseptic osteonecrosis

Abstract: Two escBEACOPP plus six sBEACOPP is efficacious in advanced-stage high-risk HL. We document a high incidence of aseptic bone necrosis, possibly related to prednisolone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In a retrospective review of adult cHL patients treated in German Hodgkin Study Group trials, the cumulative incidence of osteonecrosis was 0·93% and was more frequent in male patients. Osteonecrosis was not specifically assessed in these studies and the true rate may be higher as indicated by a small series reporting a rate of 21% (Fosså et al , , Borchmann et al , ). Osteonecrosis has not been specifically reported in the GPOH paediatric trials.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective review of adult cHL patients treated in German Hodgkin Study Group trials, the cumulative incidence of osteonecrosis was 0·93% and was more frequent in male patients. Osteonecrosis was not specifically assessed in these studies and the true rate may be higher as indicated by a small series reporting a rate of 21% (Fosså et al , , Borchmann et al , ). Osteonecrosis has not been specifically reported in the GPOH paediatric trials.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to the fact that only 7 Hodgkin lymphoma patients were included, MRI of the lower extremities only was undertakenin that study (Niinimäki et al , ). Fosså et al () evaluated the effects of 2 cycles of escalated bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, prednisolone (BEACOPP) followed by 6 standard BEACOPP cycles in 47 adult patients with advanced‐stage Hodgkin lymphoma with an international prognostic score ≥4; symptomatic osteonecrosis was diagnosed in 10 (21%) patients. Three of these 10 patients underwent hip replacement surgery after treatment (Fosså et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Fosså et al () evaluated the effects of 2 cycles of escalated bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, prednisolone (BEACOPP) followed by 6 standard BEACOPP cycles in 47 adult patients with advanced‐stage Hodgkin lymphoma with an international prognostic score ≥4; symptomatic osteonecrosis was diagnosed in 10 (21%) patients. Three of these 10 patients underwent hip replacement surgery after treatment (Fosså et al , ). However, that study did not include any children, and only performed MRI directed to the site of complaints in symptomatic patients (Fosså et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of WB-MR, especially fused with PET in FDG-PET/MR, in breast cancer imaging is being investigated over the last few years, with promising preliminary results (29); instead, WB-MR has already a well-established role in lymphoma imaging. Its high contrast resolution enables an excellent evaluation of bone marrow, allowing a reliable evaluation marrow lymphomatous involvement (30) and the early identification of osteonecrotic lesions, which are @ C I C E d i z i o n i I n t e r n a z i o n a l i very common in the follow-up of patients who receive chemotherapies and high doses of corticosteroids (31)(32)(33)(34)(35). Furthermore, it provides functional information regarding tissue cellularity through DWI, which is a sequence probing the motion of water molecules in intra-cellular and inter-cellular spaces.…”
Section: @ C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%